Matthew 5:17: The Jew Jesus and the Christian Understanding of “Fulfillment” - Gargiulo, Massimo (Studies in Christian-Jewish Relations, 2026)
The present study starts from the question of whether Jesus’s Jewish identity relates to the concept of the fulfillment of the Torah expressed in Matthew 5:17, and to what extent this has been taken into account in the history of the reception of the verse. The first part examines some Catholic Church documents, such as Dei Verbum and The Jewish People and Their Sacred Scriptures in the Christian Bible, showing the difficulty of a coherent reading of the Matthean text and, consequently, its reception within these documents. The rhetorical structure of Matthew’s words is then analyzed, noting how this structure—and more generally the very concept of the fulfillment of the Torah—can be situated within the Jewish context of the work. Finally, passages from Clement of Alexandria are examined, revealing that ancient Christian interpreters understood fulfillment neither in terms of replacement nor as something meant to remedy an alleged incompleteness of the Torah.